Estudo experimental da emissão dos modos TE e TM de um laser semicondutor sob realimentação ortogonal - Xavier, Mário Cesar Soares (2011)
In this work we present results of systematic experimental experiments observing the emission of semiconductor lasers under optical orthogonal feedback. Following previous work on the frequency behavior of laser diodes submitted to orthogonal feedback, we analyse the behavior of the two orthogonal polarization of the radiation. The emission has a main polarization (the so-called TE polarization) whose intensity is higher than the orthogonal one (the TM polarization). This ratio depends on the type of laser diode and we have measure ration between the two modes of about 100, 500, 800 and 1300 for different lasers, from different models and producers. We catheterize the TM mode, whose current threshold and spectral width is about the same than the main TE mode. We also analyze how the frequency shifts as a function of the feedback power, and we observed s correlation between this frequency shift and the ratio between the two polarizations. We interpreted this result as been due to the geometrical coupling of the feedback beam into the semiconductor cavity. The is a good agreement of the measurement with the calculated behavior.